ANALISIS PERFORMA KENDARAAN UTAMA FT 02 MORITA MJ 10 PKP-PK DALAM MENUNJANG KESELAMATAN PENERBANGAN DI BANDAR UDARA HALIM PERDANA KUSUMA - Arditya Ikhsan Putra Pangestu; Sundoro Sundoro; Wawan Yusmana (MANAJEMEN, 2025)
This research aims to analyze the performance of the main firefighting vehicle, Foam tender Type II Morita MJ 10 (1988), operated by the Aircraft Rescue and Fire Fighting (ARFF) unit at Halim Perdanakusuma Airport in supporting aviation safety. A descriptive qualitative method was employed through observation, interviews, and documentation. The findings indicate a significant decline in performance parameters such as Acceleration, top speed, and discharge rate, all of which fall below the operational standards set by Regulation PR 30 of 2022. The vehicle's age—over 35 years—has contributed to decreased technical reliability and effectiveness, particularly in emergency response situations. The study concludes that vehicle rejuvenation or replacement is urgently needed to ensure optimal readiness and safety in airport emergency operations.